Новий тип координації карбациламідофосфатного ліганду: будова та властивості комплексу срібла (I) з диметил-N-трихлороацетиламідофосфатом - Труш, В.О.; Домасевич, К.В.; Амірханов, В.М. (Видавничий дім "Академперіодика" НАН України, 2007)
A new coordination compound of silver (I) with dimethyl-N-trichloroacetylamidophosphate [L]– has been obtained. Based on IR data, the N-coordination mode of the carbacylamidophosphate ligand is suggested. The crystal structure of Na[AgL2]·CH3CN has been determined. The complex crystallizes in the trigonal system: b = 20.353(3) nm, c = 30.514(6) nm, Z = 18; space group R3c. The substance has ionic structure, the ligands are coordinated in the monodentate form via the nitrogen atoms with the formation of the complex anion [AgL2]–: the silver atom has a coordination number (CN) equal to 2, the angle N–Ag=N´ is 163.4(3)°. The sodium ion contacts with the oxygen atoms of C(O) and P(O) groups forming the six-membered chelate metallocycles: CN = 6.